2018
DOI: 10.1155/2018/2453265
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Atherogenic Indices Fluctuation in Rheumatoid Arthritis Patients on Long-Term Tocilizumab Treatment

Abstract: Rheumatoid arthritis (RA) patients are at high risk of cardiovascular (CV) events, and the chronic inflammatory state may generate quantitative and qualitative changes in lipoprotein fractions. The anti-IL-6 receptor tocilizumab (TCZ), even if effective in inflammation and joint damage prevention, determined significant alterations to RA patients' lipid levels in randomized controlled trials, but real-world data are lacking. We evaluated the changes in lipid fraction levels and disease activity in a longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
5
24
0
1
Order By: Relevance
“…As expected and as previously reported [ 18 , 42 ], lipid parameters increased during TCZ treatment, especially total and LDL cholesterol without alteration of atherogenic index. However, these changes are complex and inflammation itself has a wide range of consequences on lipids, lipoproteins and associated molecules as exemplified by the lipid paradox [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…As expected and as previously reported [ 18 , 42 ], lipid parameters increased during TCZ treatment, especially total and LDL cholesterol without alteration of atherogenic index. However, these changes are complex and inflammation itself has a wide range of consequences on lipids, lipoproteins and associated molecules as exemplified by the lipid paradox [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…[42][43][44] On the other hand, the association of DAS-28 and VLDL-C levels is not clear yet, but it has been reported that RA patients with high disease activity had alterations of the lipid profile. 38,45 Rheumatoid factor (RF) correlated with age and smoking index, which agrees with other reports [46][47][48] ; likewise, RF correlated with triglycerides, which could be explained by this autoantibody´s positive correlation with a high RA disease activity, 49 a status associated with lipids alteration.…”
Section: Discussionsupporting
confidence: 89%
“…Treatment-related increases in circulating lipid levels have been observed during the long-term administration of TCZ in patients with rheumatoid arthritis (RA) ( 4 - 6 ). Cacciapaglia et al observed a significant increase in TG levels in 40 patients with RA treated with TCZ (TG, 139±13 mg/dL at baseline vs. 157±15 mg/dL at 24 weeks) compared with those in 20 RA patients who received methotrexate (TG, 126±26 mg/dL at baseline vs. 121±24 mg/dL at 24 weeks) during the first 24 weeks ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-related increases in circulating lipid levels have been observed during the long-term administration of TCZ in patients with rheumatoid arthritis (RA) ( 4 - 6 ). Cacciapaglia et al observed a significant increase in TG levels in 40 patients with RA treated with TCZ (TG, 139±13 mg/dL at baseline vs. 157±15 mg/dL at 24 weeks) compared with those in 20 RA patients who received methotrexate (TG, 126±26 mg/dL at baseline vs. 121±24 mg/dL at 24 weeks) during the first 24 weeks ( 4 ). According to Giles et al, in a randomised controlled trial comparing treatment with TCZ and etanercept for RA, patients administered TCZ showed a median increase of 13.6% and 11.1% in TG and LDL-C levels, respectively, compared to those in the etanercept arm at 4 weeks, demonstrating a significant increase ( 6 ).…”
Section: Discussionmentioning
confidence: 99%